Mengharmonisasikan Manusia dan Alam: Kajian Filsafat Relasionalitas Armada Riyanto atas Kejadian 2:6-16 - Sekundus Septo Pigang Ton (Fakultas Teologi, Universitas Sanata Dharma, 2025)
The writing of this article focuses on Harmonizing Man and Nature: Armada Riyanto's Relationality Philosophy Study on Genesis 2:6-16. The current ecological crisis is caused by human over-exploitation, such as mining, deforestation, factory waste into rivers and plastic waste. The purpose of writing this article is to harmonize nature and humans who have been destroyed by the ecological crisis. The findings are first, the similarity of the word 'Ādam םדא (Human) with the word המדא Adamā (Land) as a relation of